Essentials of managerial finance - Weston, J. Fred (Dryden Press, 1996)
The book begins with a discussion of basic concepts, including accounting statements, security markets, interest rates, taxes, risk analysis, time value of money, and the basics of security valuation. It also explains how financial managers can help their firm's values by improving decisions in such areas as workingcapital management, capital budgeting, and choice of capital structure